Gravity investigation in the Ikh Bogd faults - Bazar, Buyantogtokh; Davaasambuu, Battogtokh; Tsend-Ayush, Nyambayar; Myagmar, Dorjdavaa; Gantumur, Buyankhishig (Mongolian Journal of Astronomy and Geophysics, 2024)
On December 4, 1957, a moment magnitude (Mw) 8.1 earthquake generated approximately 270 km of surface rupture along the Ikh Bogd Fault, situated within the Gobi-Altai Mountain Range. As part of the research initiative titled “Methodology for Determining Parameters of Active Faults That Are Not Visible on the Surface”, a gravity survey was conducted at three strategically selected sites: Site 1 – Toromkhon Sair, Site 2 – Dalanturuu Foreberg, and Site 3 – Builsnii Zadgai Sair, all located in proximity to the Ikh Bogd Mountain. Gravimetric data acquired from these sites facilitated the delineation of subsurface geological boundaries and enabled the identification of fault continuations that are not not visible on the Surface. Bouguer anomaly data are analyzed at the three sites to investigate features of the active fault zones, including continuity, segmentation, and faulting type. Several derivatives and structural parameters derived from the gravity gradient are applied to enhance the visibility of these features. In particular, the first horizontal and vertical derivatives, together with the normalized total horizontal derivative, effectively characterize the continuous subsurface fault structures along the fault zone.